Analisis Faktor-Faktor yang Mempengaruhi Minat Nasabah dalam Menggunakan Mobile Banking Syari’ah: (Studi Kasus Guru Pondok Modern Darussalam Gontor Kampus 12) (Prosiding Keislaman dan Sains, 2025)
In today's information era, consumer behavior has changed a lot in making transactions, consumers prioritize aspects of convenience, flexibility, efficiency, and simplicity. The rapid development of information technology affects almost all aspects of human life and activities. However, it has not happened among PMDG Campus 12 teachers in using Syari'ah M-Banking. This study aims to determine the effect of usefulness, convenience, and trust on customer interest in using Syari'ah M-Banking partially or simultaneously. This study uses a quantitative approach that uses descriptive research methods. The results of this study indicate that trust has a positive and significant effect partially on customer interest in using Syari'ah M-Banking on teachers at Pondok Modern Darussalam Gontor Campus 12, while usefulness and convenience do not have a significant effect on customer interest in using Syari'ah M-Banking on teachers at Pondok Modern Darussalam Gontor Campus 12. Simultaneously, usefulness, convenience, and trust have a significant effect on customer interest in using Islamic M-Banking for teachers at Pondok Modern Darussalam Gontor Campus 12. The contribution given by the variables of usefulness, convenience, and trust is shown by the ability to influence the variation of the increase and decrease in customer interest in using Islamic M-Banking which is 48.4%.
Keywords: Usefulness; Convenience; Trust; Customer Interest